2015
DOI: 10.1186/s13058-014-0513-8
|View full text |Cite
|
Sign up to set email alerts
|

Loss of periostin/OSF-2 in ErbB2/Neu-driven tumors results in androgen receptor-positive molecular apocrine-like tumors with reduced Notch1 activity

Abstract: IntroductionPeriostin (Postn) is a secreted cell adhesion protein that activates signaling pathways to promote cancer cell survival, angiogenesis, invasion, and metastasis. Interestingly, Postn is frequently overexpressed in numerous human cancers, including breast, lung, colon, pancreatic, and ovarian cancer.MethodsUsing transgenic mice expressing the Neu oncogene in the mammary epithelium crossed into Postn-deficient animals, we have assessed the effect of Postn gene deletion on Neu-driven mammary tumorigene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 75 publications
0
14
0
Order By: Relevance
“…Moreover, CK5 has been proposed by some authors to be a marker that determines basal-like features of breast cancer, along with ER, PR, HER2, and EGFR [ 86 ]. Several of the most important markers with prognostic and therapeutic values in breast cancer are summarized in Table 1 [ 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 114 115 116 117 118 119 120 121 122 123 124 125 126 127 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 ].…”
Section: Controversial Markers Of Normal Breast Tissue With Potentialmentioning
confidence: 99%
“…Moreover, CK5 has been proposed by some authors to be a marker that determines basal-like features of breast cancer, along with ER, PR, HER2, and EGFR [ 86 ]. Several of the most important markers with prognostic and therapeutic values in breast cancer are summarized in Table 1 [ 87 88 89 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 112 113 114 115 116 117 118 119 120 121 122 123 124 125 126 127 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 ].…”
Section: Controversial Markers Of Normal Breast Tissue With Potentialmentioning
confidence: 99%
“…Furthermore, periostin interacts with various molecules to affect a number of pathways, such as Notch 1 signaling (9,10), and thus, a lack of periostin may be responsible for a suppression of Notch 1 signaling (9,10). Conversely, it cannot be excluded that the overexpression of periostin may result in the activation of Notch 1 signaling in cancer (10). Additionally, periostin was identified as being involved in gastric cancer cell epithelial-mesenchymal transition (EMT) (11).…”
Section: Introductionmentioning
confidence: 99%
“…Periostin is a secreted matrix N‐glycoprotein that plays vital roles in numerous cancers, especially in gastrointestinal malignancy . For pancreatic cancer, it is reported that POSTN has a biphasic effect on cell migration and correlates with the epithelial to mesenchymal transition of human pancreatic cancer cells, participates in the process of tumor angiogenesis, and could promote invasiveness and resistance of pancreatic cancer cells to induce cell death .…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In the present study, we identified that POSTN and CA242 could be potential diagnostic Periostin is a secreted matrix N-glycoprotein that plays vital roles in numerous cancers, especially in gastrointestinal malignancy. 16,20,[22][23][24][25][26] For pancreatic cancer, it is reported that POSTN has a biphasic effect on cell migration and correlates with the epithelial to mesenchymal transition of human pancreatic cancer cells, 17 participates in the process of tumor angiogenesis, 16 and could promote invasiveness and resistance of pancreatic cancer cells to induce cell death. 17,27 12 They reported a high correlation between the serum levels of CA242 and CA19.9, which is consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%